Spectrophotometric Determination of Chlorpromazine Hydrochloride Using 4-Nitroanilline by Oxidative Coupling Reaction (Baghdad Science Journal, 2019)
A simple, rapid spectrophotometric method has been established for the determination of chlorpromazine hydrochloride (CPZ) in its pure form and in a tablet formulations. The suggested method is based on the oxidative coupling reaction with4-nitroainlline using KIO3 in acidic solution to produce a violet colored product with maximum absorption at λ=526 nm.The analytical data obtained throughout this study could be summarid as follows: 1ml of 1M HCl (pH=2.2), 1 ml of 4-nitroanilline (1x10-2M), and 1.5ml of (1x10-2)KIO3 per 25 ml reaction medium. The order of additions, coupling reaction time, and temperature in addition to the type of solvent were studied.The Beer′s law is obeyed over the concentration range of(5–40) µg ml-1, but the detection limit and quantification limit are 0.34 besides 1.03 µg ml-1 respectively. The correlation coefficient (r) for the calibration graph was found to be 0.9980, molar absorptivity of 10. 25 × 103 L.mol -1.cm-1, and Sandell′s sensitivity index of 0.03467 µg.cm-2. The precision and accuracy of the method were tested by calculating the percentage of relative standard deviation (RSD%) (<1.831%) and the average recovery percent (99.22%) average error percent Erel%(0.558).Direct and standard addition procedures were applied to both standards and specimens of pharmaceutical and the results indicate that the suggested method was successfully applied for the determination of CPZ.